Biossegurança no patenteamento de tecnologia transgênica contida em sementes: uma visão a partir da função socioambiental da propriedade intelectual - Ferreira, Maria Paula da Rosa (2018)
This work analyzed the relationship between biosafety in the patenting of transgenic technology contained in seeds and the fulfillment of the socioenvironmental function of intellectual property. As specific objectives, it was established: to present a theoretical conceptual framework of the current patent system of transgenic technology contained in seeds, duethe economic-market bias; to verify the socioenvironmental function of intellectual property through the regulation of biosafety and the challenges in the Brazilian legal system to reshape the market vision; and to demonstrate the prospects of guaranty the socioenvironmental function of the intellectual property of transgenic technology contained in seeds in Brazil today. The paper sought to solve the following research problem: What are the perspectives for the effectiveness of the socio-environmental function of intellectual property based on the adoption of biosafety measures and restrictions in the analysis of concessions / use of patents for transgenic technology in Brazil today? To answer this question, we used the dialectical approach and the complex- systemic theory based on Fritjof Capra and Edgar Morin, in view of the use of systematic formulations in the approach regarding the patenting of transgenics evaluated under the agronomic approach, economic, social, ethical and legal. As a procedure, was made analysis bibliographic and of documents of the National Institute of Industrial Property applied to patent 0016460-7 of the soybean Intacta RR2 Pro in Brazil. As a technique was realized the production of files, reviews, abstracts, expanded abstracts and data collection in database. In view of the above, it was concluded that attention to biosafety measures as a means of effecting the socio-environmental function of industrial property permeates the preservation of the general interests of the social and environmental collectivity. It was observed that only a technoscience that pay attention in life, through effective biosafety measures, will demonstrate a true and profitable triumph of biotechnology in the agrifood sector.